“Amar te Duele” (“Love Hurts”): Sexual relationship power, intimate partner violence, depression symptoms and HIV risk among female sex workers who use drugs and their non-commercial, steady partners in Mexico - Ulibarri, Monica D. (2015)
A significant body of research among female sex workers (FSWs) has focused on individual-level HIV risk factors. Comparatively little is known about their non-commercial, steady partners who may heavily influence their behavior and HIV risk. This cross-sectional study of 214 FSWs who use drugs and their male steady partners aged ≥18 in two Mexico-U.S. border cities utilized a path-analytic model for dyadic data based upon the Actor-Partner Interdependence Model to examine relationships between sexual relationship power, intimate partner violence (IPV), depression symptoms, and unprotected sex. FSWs’ relationship power, IPV perpetration and victimization were significantly associated with unprotected sex within the relationship. Male partners’ depression symptoms were significantly associated with unprotected sex within the relationship. Future HIV prevention interventions for FSWs and their male partners should address issues of sexual relationship power, IPV, and mental health both individually and in the context of their relationship.